2011
DOI: 10.1080/09243453.2011.589859
|View full text |Cite
|
Sign up to set email alerts
|

Improving attainment across a whole district: school reform through peer tutoring in a randomized controlled trial

Abstract: 2011) 'Improving attainment across a whole district : school reform through peer tutoring in a randomized controlled trial.', School eectiveness and school improvement., 22 (3). pp. 265-289. Further information on publisher's website: This is an electronic version of an article published in Tymms, P. and Merrell, C. and Thurston, A. and Andor, J. and Topping, K. and Miller, D. (2011) 'Improving attainment across a whole district : school reform through peer tutoring in a randomized controlled trial.', Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 39 publications
(39 reference statements)
7
60
1
1
Order By: Relevance
“…It should be noted that meta-regressions have very weak statistical power a low number of studies. Regarding this apparent lack of doseresponse relationship in tutoring, the findings of this review are in line with results of recent large-scale randomized trial of peer tutoring study in Scotland, The Fife Peer Learning Trial (Tymms, Merrell, Thurston, Andor, Topping & Miller, 2011). A no-intervention control group was absent, and the different groups served as controls to each other (e.g.…”
Section: Social Self-concept and Behavioural Outcomessupporting
confidence: 82%
See 1 more Smart Citation
“…It should be noted that meta-regressions have very weak statistical power a low number of studies. Regarding this apparent lack of doseresponse relationship in tutoring, the findings of this review are in line with results of recent large-scale randomized trial of peer tutoring study in Scotland, The Fife Peer Learning Trial (Tymms, Merrell, Thurston, Andor, Topping & Miller, 2011). A no-intervention control group was absent, and the different groups served as controls to each other (e.g.…”
Section: Social Self-concept and Behavioural Outcomessupporting
confidence: 82%
“…Ritter and Maynard also concluded that highly structured tutoring programs are more likely to lead to improved reading. Similar phenomenon was observed in the Fife Peer Learning study, which reported Effect Sizes of 0.2-0.25 for highly structured peer tutoring in mathematics (Tymms et al, 2011). The impact of structure shows the important role that an educator has in designing tutoring programs to ensure that interactions maximize the behaviours seen as providing effective learning.…”
Section: Implications For Implementation Of Tutoring Programssupporting
confidence: 73%
“…Supporting this view recent RCT studies of peer tutoring have reported lower ESs than a study using the same tutoring techniques in studies when randomisation was not used to assign to condition. For example, the Fife Peer Learning project where tutoring in reading and maths was implemented over two years in a RCT reported a mean ES of 0.20-0.25 Tymms, Merrell, Thurston, Andor, Topping & Miller, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Positive results have been reported in the USA and UK (Parsons et al ., ). Cross‐age peer mentoring has had a positive effect in reading and mathematics on the learning of both the mentee and the mentor, provided the age gap between the two is at least 2 years (Topping et al ., ; Tymms et al ., ). Subject‐specific mentoring has been shown to function as a useful buffer to the more general challenges faced by those in transition to secondary school (Thurston et al ., ).…”
Section: Discussionmentioning
confidence: 97%